Cardiocutaneous Syndrome: The Tale between Heart and Skin - A K M Monwarul Islam; Amiruzzaman Khan; Zakir Hossain (Global Journal of Rare Diseases - Peertechz Publications, 2017)
Cardiocutaneous syndromes are rare, genetically determined disorders in which arrhythmogenic cardiomyopathy is accompanied by characteristic cutaneous phenotypes of woolly hair and palmoplantar keratoderma. Pattern of cardiac involvement differs in different cardiocutaneous syndromes; right ventricle (RV) is predominantly affected in the form of classical arrhythmogenic right ventricular cardiomyopathy/ dysplasia (ARVC/D) in Naxos disease whereas the left ventricle (LV) is mainly involved in the form of dilated cardiomyopathy in Carvajal syndrome. Both conditions are transmitted in autosomal recessive manner, and results from mutations in cell adhesion molecules compromising the integrity of desmosomal junctions of skin and myocardium. Naxos disease usually presents by adolescence with malignant ventricular arrhythmia or cardiac arrest whereas Carvajal syndrome is manifested earlier with heart failure. Cardiomyopathy is diagnosed by the 2010 Task Force Criteria. Implantation of automated implantable cardioverter-defibrillator (AICD) forms the mainstays of treatment by preventing sudden cardiac death. Genetic testing is available. Several international databases and registries, often as a part of other genetically determined arrhythmogenic disorders, are directed to better characterize and manage these cardiocutaneous syndrome patients.